Salute renale per tutti e ovunque: riflessioni al femminile sul tema centrale della Giornata Mondiale del Rene 2020 - Anna Laura Fantuzzi; Elisa Berri; Lida Tartaglione; Rossella Giannini; Sara Dominjianni; Silvia Porreca (AboutScience Srl, 2020)
The goal of the World Kidney Day 2020 (WKD) is "the promotion of public health by ensuring universal, equitable and sustainable access to care, making access to health for all people and social categories equitable". Chronic Kidney Disease (CKD) is a complex and "demanding" health problem for patients and professionals, particularly in the more advanced stages of the disease. In addition to factors such as the so-called systemic conditions and risk factors, sex-related factors intervene in women, which can further complicate the CKD trend. For these reasons, one of the objectives of the World Kidney Day is that prevention and early treatment are included in the Universal Health Coverage (UHC) and that common strategies are implemented to promote awareness of this pathology. The woman has always played a central role in the "coordination" of family life and "taking care", a role transversal to the different ethnic groups, as evidenced also by the data relating to living kidney donation. This article gives a reflection on some issues related to prevention and treatment of CKD from a female perspective, such as what strategies to identify to implement prevention in the family starting from nutrition, such as the advice for the preparation of a diet plan respectful of the traditions of the country of origin, the identification and treatment of risk factors in order to implement strategies aimed at prevention dedicated to the female world and which style distinguishes the female approach to care | (Gender_nephrology)